1999
DOI: 10.1016/s8756-3282(99)00021-6
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of osteoporotic cancellous bone

Abstract: To investigate the mechanism underlying femoral neck fracture, it is necessary to determine the various mechanical properties, including the bone strength, of the primary compressive group. We investigated the mechanical anisotrophy of the primary compressive group by comparing differences in its mechanical properties, depending on the loading direction. Twenty-three femoral heads of 20 female and 3 male patients with femoral neck fracture were studied. The mean age of these patients was 79.9 years (range, 63-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 12 publications
2
16
0
Order By: Relevance
“…We may hypothesize that with the development of the osteoporosis the environment probed by water restricted between fat and bone becomes more isotropic due to the structural rearrangement of the endosteum cell lines or of the trabeculae surface. On the other hand, using a different length scale of the order of millimeters, trabecular bone anisotropy increases with osteoporosis, as well documented in literature [48,49]. Our findings suggest that, with the development of osteoporosis, both of these mechanisms occur, at different length scales.…”
Section: Discussionsupporting
confidence: 85%
“…We may hypothesize that with the development of the osteoporosis the environment probed by water restricted between fat and bone becomes more isotropic due to the structural rearrangement of the endosteum cell lines or of the trabeculae surface. On the other hand, using a different length scale of the order of millimeters, trabecular bone anisotropy increases with osteoporosis, as well documented in literature [48,49]. Our findings suggest that, with the development of osteoporosis, both of these mechanisms occur, at different length scales.…”
Section: Discussionsupporting
confidence: 85%
“…Anisotropy is constituted under the influence of strengths applied to bone and permits establishing resistance to these strengths in a given preferential direction. Sugita et al [16] observed variations in bone strength following the loading directions. These variations were interpreted as an anisotropic feature of the bone strength, and trabecular anisotropy might be considered to predict the fracture risk.…”
Section: Technical Considerationmentioning
confidence: 99%
“…An important microarchitecural property of trabecular bone is the anisotropy of the structure, defined by the existence of preferential direction(s) in the trabecular organization. Anisotropy of trabecular bone tissue primarily involves the preferential orientation(s) of trabeculae and is also reflected by the oriented values of bone strength [16]. Anisotropy is constituted under the influence of strengths applied to bone and permits establishing resistance to these strengths in a given preferential direction.…”
Section: Technical Considerationmentioning
confidence: 99%
“…Mineral content was analysed in femora and lumbar vertebrae as representing predominantly cortical and trabecular bone, respectively. Furthermore, these bones are characterised by different physical loading and mechanical anisotropy (Sugita et al 1999), which may be important factors for determining the target of mineralization. The hypothesis was that oligofructose impedes ovariectomy-induced loss of bone mineral content and preserves bone architecture due to stimulated apparent Ca absorption.…”
mentioning
confidence: 99%